Adsorption of three selected flavonoids with humic fraction‐modified silica gel in hexane: A mechanism study. Issue 9 (12th April 2020) - Chen, Shushi
Abstract: Three selected flavonoids, commonly found in spices, red‐purple fruits, and vegetables, were adsorbed on humic fraction‐modified silica gel in hexane. The percentage of adsorption in hexane for all examined analytes was nearly 100% after 1 hr, as a result of the strong dipole–dipole interaction. The increasing amount of adsorbent involved in the process improved the percentage of adsorption, which in turn shortened the time needed to reach the maximum by providing more binding sites. However, adsorption was not observed in other liquid phases under the same conditions, such as acetonitrile and ethyl ether. The mechanism leading to the adsorption was explored chromatographically, as well as by fourier transform infrared spectroscopy (FTIR) and theoretical simulations. Abstract : 3D ball‐and‐stick model showing the difference in the spatial orientation for flavanone and flavone